PENDIDIKAN MULTIKULTURAL DALAM KURIKULUM PAI - Ridhwan, Burhanuddin; Syamsuddin; Hanifuddin (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2020)
An educational approach with a multicultural insight can provide awareness and appreciation of cultural, ethnic, and religious diversity in forming a lifestyle of unity andtogetherness in a life of peace and mutual respect, andfollowing the diversity of our society. The focus of theproblems in this study are: First: the PAI learning system in amulticultural education curriculum. The method used in thisresearch is library research or literary study, which is a studycarried out to solve a problem based on a critical and in-depthstudy of relevant library materials following the focus of theresearch. The results of this study, first: The PAI learningsystem in the multicultural education curriculum can conditionstudents to learn to live in differences, build mutual trust,maintain mutual understanding, uphold mutual respect, openthinking, appreciation and interdependence, and conflictresolution